CLADAG 2021 BOOK OF ABSTRACTS AND SHORT PAPERS 13th Scientific Meeting of the Classification and Data Analysis Group - Firenze, September 9-11, 2021 - PORZIO, Giovanni Camillo; RAMPICHINI, CARLA; Bocci, Chiara (Proceedings e report, 2021)
The book collects the short papers presented at the 13th Scientific Meeting of the Classification and Data Analysis Group (CLADAG) of the Italian Statistical Society (SIS). The meeting has been organized by the Department of Statistics, Computer Science and Applications of the University of Florence, under the auspices of the Italian Statistical Society and the International Federation of Classification Societies (IFCS). CLADAG is a member of the IFCS, a federation of national, regional, and linguistically-based classification societies. It is a non-profit, non-political scientific organization, whose aims are to further classification research.